Existing information gap for decentralised development - a synoptic view - Mohan, A. (2003)
The necessity of data/information, the existing Statistical System in India and the Major National agencies and Local level departments for data sources for decentralised development are dealt with. To understand the situation of data availability to the extent possible and the existing information gap in various sectors of the district economy as well as in the planning process in the decentralised spatial units an assessment has been made. This has been highlighted in four major categories viz. Time delay in publication of data, Data redundancy and non-comparability, Non-availability and non-utilisation of data and Data confidentiality. - Reproduced.
Keywords: Decentralization